Why do individuals suffer during unemployment? Analyzing the role of deprived psychological needs in a six-wave longitudinal study. - Zechmann, Andrea; Paul, Karsten (Journal of Occupational Health Psychology, 2019)
This 6-wave study addresses the psychological meaning of employment by examining the psychological need mechanisms predicting psychological distress during unemployment and reemployment. According to the deprivation model, unemployed people suffer, as unemployment deprives them of the latent functions of employment (i.e., time structure, social contact, status, activity, and collective purpose), which reflect psychological needs that are important for mental health. We tested whether the latent functions of employment, the manifest function of employment (i.e., one’s financial situation), and the additional psychological need functions of competence and autonomy mediate the associations between unemployment and distress. At Time 1, N 1,061 participants, who were either unemployed or lost their jobs during the course of the study, took part. At Time 6, after two and a half years, 45.4% of the respondents were employed. Multilevel mediation analyses showed that reemployment predicted gains in each of the original latent and manifest functions, which, in turn, predicted reductions of distress. Collective purpose was found to be the most important latent function. The findings endorse the validity and robustness of the deprivation model. Additionally, they demonstrate that the neglected psychological need function of competence (but not autonomy) also is a latent function of employment that should be incorporated into the deprivation model. Contrary to the predictions of the deprivation model, we found that poverty also plays an important role for the distress associated with unemployment. <br
Keywords: unemployment; mental health; latent functions; deprivation; financial strain